The Role of the International Olympic Committee (IOC) on United StatesChina Bilateral Relations, Case Study: Beijing 2022 Winter Olympic Games - Siti Rabbani Hakim (Mediasi: Journal of International Relations, 2021)
Sport is one of the marginalized issues, with the globalization of sport beginning to be consideredas a means of uniting society and repairing the rift that occurred after the conflict, eithersymbolically or by holding sports agendas to campaign for peace and development. TheInternational Olympic Committee (IOC) is an organization formed to revive the Ancient GreekOlympics and serves as an observer of the Modern Olympics which are held every four years. The2022 Winter Olympics to be held in Beijing has a strong political background. This makes it arecreation of the Berlin Summer Olympics in 1936 under the Nazi leadership, as well as theOlympics to be held in Beijing in 2022. At the time of the Olympics, the Chinese Communist Partyused the Olympics as an opportunity to express its desire to gain status in the international order,this was hampered by the diplomatic boycott sent by the United States government against theOlympics, causing a rift in relations between the United States and China during the Olympics.Thus, this research aims to find out how the dynamics of bilateral relations between the UnitedStates and China and the reasons for the US to conduct a Diplomatic Boycott of the WinterOlympics. In addition, this study will also examine how the role of the IOC as a mediator inhandling conflicts between countries concerned with the Olympics. This research uses a qualitativemethod in analyzing the role of the IOC in handling bilateral conflicts between the US and Chinaat the 2022 Winter Olympics. Analysis of the role of institutions in this study uses the role ofinstitutions developed from Liberal Institutional theory. From this analysis, it can be concludedthat the IOC succeeded in maintaining peace during the Olympics. However, despite all the effortsmade by the IOC, the United States Government still refused to present its diplomatic officialsduring the Olympics.